Mortality and Causes of Death in Inherited Antithrombin Deficiency - van Boven, H H; Vandenbroucke, J P; Westendorp, R G J; Rosendaal, F R (Thrombosis and Haemostasis, 1997)
To assess the contribution of inherited antithrombin deficiency to mortality, we investigated the causes of death in 14 families with inherited antithrombin deficiency. Between 1830 and 1994, 86 of 266 family members who had a probability of 0.5 or more for heterozygosity died. The causes of death were obtained for 58 of 66 deaths occurring between 1940 and 1994. Standardized mortality ratios (SMR) were calculated using mortality rates from the general population adjusted for age, sex and calendar period.The overall SMR was 0.90 from 1830 to 1994 (95% C.1.0.72-1.11). From 1940 until 1994 44 men and 22 women died (SMR = 1.09, 95% C.I. 0.84-1.39; SMR men = 1.20, 95% C.I. 0.87-1.61; SMR women = 0.92,95% C.I. 0.58-1.39). No excess mortality compared to the general population was found for cancer (14 deaths) or circulatory diseases (28 deaths). A slightly increased mortality caused by respiratory diseases (7 deaths, SMR = 1.68,95% C.I. 0.68-3.47) seemed due to pneumonia (4 deaths, SMR = 2.86, 95% C.I. 0.78-7.32). Venous thromboembolic complications were listed once in association with a risk situation, and one other death could be attributed to fatal pulmonary embolism. Cerebral hemorrhages were listed three times. It could not be verified whether these hemorrhages were related to anticoagulant therapy; the frequency was slightly higher than the expected population figure (SMR = 1.49,95% C.I. 0.31-4.36). The mean age of death for all causes was 64 years; the two fatal thromboembolic episodes occurred at age 20 and 30 years.The data show that antithrombin deficiency is associated with a normal survival and a low risk of fatal thromboembolic events. The use of long-term anticoagulant treatment in asymptomatic individuals should be considered carefully in view of the greater risk of fatal bleeding associated with long-term anticoagulant prophylaxis.